JENIS, HARGA KAYU KOMERSIL DAN ANALISIS EKONOMI PADA INDUSTRI KAYU SEKUNDER (PANGLONG) DI KABUPATEN KARO ( - Bhima mahawira; Tito Sucipto; Rudi Hartono (Program studi Kehutanan USU, 2016)
This research aimed to determine the type and price of commercial timber traded in Karo district. This research investigated the secondary wood industry usually called “panglong” as an object as well as the source of information. This research was conducted by the observation to secondary wood industry in 17 districts of Karo. Data include the type, size, and price of wood, then data was tabulated. Then, the economic analysis for secondary industry wood was performed. The analysis results of 17 from industry surveyed in Karo district showed that the type of wood being traded were dominated by any kind of hard wood with percentage of 100%, pine (Pinus merkusii) of 88.23%, any hard woods of 76.47%, and meranti (Shorea sp) and dammar (Shorea macroptera) of 23.52%. Pine has the cheapest price among the commercial timber species that are traded others. Traded timber prices ranging from Rp. 10000 to Rp 11000 per inch. The greater secondary wood sawmill is UD. Surbakti with 25 employees and the BEP value of door frame production are Rp. 572625/ product, window sills Rp. 574875/product, while the smallest is UD. Mual Nauli with 2 employees and BEP value of window sills are Rp 250000 / product and ventilation Rp 62500 / product.Keywords: Secondary Wood Industry, Panglong, Economic Analysis.